Evaluating suggested stricter gamma criteria for linac-based patient-specific delivery QA in the conventional and SBRT environments. (August 2022) - Price, Robert A.; Veltchev, Iavor; Lin, Teh; Eldib, Ahmed; Chen, Lili; Jin, Lihui; Chen, Xiaoming; Liu, Jie; Wang, Lu; Ma, C.-M. Charlie
Highlights: Stricter γ criteria may have practical implications including treatment start delays. VMAT site-specific delivery QA tolerance limits are unnecessary. IMRT/VMAT QA passing rate and plan complexity do not correlate over the range studied. VMAT SBRT QA passing rates do not correlate with target volume over the range studied. Abstract: Purpose: To evaluate AAPM TG-218 recommended tolerances for IMRT QA for conventional and SBRT delivery. Methods: QA analysis was repeated for 150 IMRT/VMAT patients with varying gamma criteria. True composite delivery was utilized, corrected for detector and output variation. Universal tolerance (TLuniv ) and action limits (ALuniv ) were compared with statistical process control (SPC) TLSPC and ALSPC values. Analysis was repeated as a function of plan complexity for 250 non-stereotactic body radiotherapy (SBRT) VMAT patients at 3%/2mm and a threshold of 10% and for 75 SBRT VMAT patients at 2%/2 mm and a threshold of 50% with results plotted as a function of PTV volume. Regions of failure were dose-scaled on the planning CT data sets based on delivery results. Results: The IMRT/VMAT TLSPC and ALSPC for gamma criteria of 3%/3 mm were 96.5% and 95.6% and for 3%/2 mm were 91.2% and 89.2%, respectively. Correlation with plan complexity for conventional fractionation VMAT was "low" for all sites with pelvis having the highest r value at −0.35. The equivalent SBRT PTV diameter ranged from 2.0 cm to 5.6 cm. Negative low correlation was found for 38 of 75 VMAT cases below ALuniv . Conclusions: The ALuniv and ALSPC are similar for 3%/2 mm. However, our 5% failure rate for ALuniv, may result in treatment start delays approximately 2 times/month, given 40 new cases/month. VMAT QA failure at stricter criteria did not correlate strongly with plan complexity. Site-specific action limits vary less than 3% from the average. SBRT QA results do not strongly correlate with target size over the range studied.